Night-owls and larks: shedding light on cultural competence in translator training - Chumbo, Isabel (2019)
Translator training is viewed as highly practical. However, future translators are also trained through theoretical approaches and with a strong focus on the acquisition of a set of competences which will make their future as professionals uncomplicated. One of these competences includes cultural knowledge. Cultural competence is a fundamental skill of communication in a multicultural world, revealing itself paramount in the understanding of any type of text the translator has to deal with. Therefore, developing and consolidating this competence should be a major concern when training future translators. The aim of this article is to shed light on the acquisition, use and practice of cultural competence. Based on the Task-based learning teaching (TBLT) methodology and taking into account the different learning styles of our students, several text types and genres were analysed in the English language course of a master’s degree in Translation in Portugal, namely through literary texts and the language of headlines. We shall then present some diagnosed and identified problems students felt during hands-on work focusing on this competence, convey some examples that have been worked upon and finally give recommendations on how to overcome this constraint in both learning and teaching perspectives.